7-2k=13

Simple and best practice solution for 7-2k=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-2k=13 equation:


Simplifying
7 + -2k = 13

Solving
7 + -2k = 13

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -2k = 13 + -7

Combine like terms: 7 + -7 = 0
0 + -2k = 13 + -7
-2k = 13 + -7

Combine like terms: 13 + -7 = 6
-2k = 6

Divide each side by '-2'.
k = -3

Simplifying
k = -3

See similar equations:

| -12a+194=-5a+152 | | 2(2x+15)4x=180 | | 5x-2y=7x+8 | | 19=9-2z | | 10+2k=4 | | 5x+9=3*-6 | | x-5=-13+x+5+x | | 10x-6-7x=3-6x | | 3(x+14)=5x-12 | | 3(-p-4)=-6(2+2p)+2p | | 5x+5x+7x+7x+8x+8x=720 | | 2(1+4v)=8+7(v-1) | | x=2-9x+20 | | X^2+29x-132=0 | | 25X=350 | | -8a-18=-2(-5+2a) | | 5k+7=2(k-1) | | -4a-6(6a+1)=-8(3+5a) | | 4-7b=-3b | | b^2+b+4=-b^2 | | -10-8=2d-8d+108 | | 3x^2-528=0 | | f(x)=(x-5)(x-(-3))(x-(-1+3i))(x-(-1-3i)) | | 1-3(1-4n)=12n-26 | | z^2=-8-6i | | 5c+7=17 | | 2x-0.8=2.4 | | -5x^2+10x=-15 | | X^2+41x-132=0 | | 5x+9y=-75 | | 7k-21=7(k-3) | | 2x^2+12y^2-8x-12y+11=0 |

Equations solver categories